Underreporting of Food Intake among Mexican/Mexican-American Women: Rates and Correlates - Bothwell, Elizabeth K.G. (2009)
BACKGROUND: Underreporters are those individuals who report a dietary intake level that is not biologically plausible given their physiological status and physical activity level. Underreporting of food intake threatens the validity of dietary assessment; yet, little is known about the prevalence or correlates of underreporting in the Mexican/Mexican-American community. OBJECTIVE: To examine underreporting rates and correlates among Mexican/Mexican-American women using dietary data based on repeated 24-hour recalls and the Goldberg equation. DESIGN: Cross-sectional study of baseline data collected as part of a larger randomized controlled trial through structured interviews and anthropometrics measurements. SUBJECTS/SETTING: A random sample of 357 Mexican/Mexican-American women, ranging in age from 21 to 67 years, living in south San Diego near the U.S./Mexico border. STATISTICAL ANALYSES PERFORMED: Age, income level, education level, and weight status, all correlates of underreporting in samples of non-Hispanic white participants, were examined as potential correlates of underreporting among Mexican/Mexican-American women using binary logistic regression. Acculturation was examined to determine if it accounted for additional variance in underreporting. Finally, multivariate analyses using backward stepwise regression were conducted to determine which correlates remained significant in the final model. RESULTS: Rates of underreporting varied across the five detection methods employed, from 11.9% (n=42) to 81.3% (n=286). Obese weight status was the only significant correlate across all five underreporting detection methods and remained significant in the final model. Using backward stepwise regression, the final model showed weight status to be a significant correlate of underreporting both at the overweight (p<0.05) and obese levels (p<0.01). In addition, Anglo orientation score (p<0.05) remained significant in the final model, as well as the age group of 51 years or older (p<0.05). CONCLUSIONS: Consistent with previous studies, underreporters in this Mexican/Mexican-American sample were more likely to be overweight or obese, and were older. They also were more likely to identify with the dominant Anglo culture. Additional studies are needed to further examine underreporting error in dietary assessment among Latinos, and to determine whether the effects of acculturation on underreporting are found in other Latino subgroups.